(untitled) (Research, Society and Development, 2022)
Objective: to analyze the economic losses and impacts for the floriculture of Vargem Alta, in the Nova Friburgo neighborhood of Rio de Janeiro, Brazil. Methods: documentary and descriptive study using hemerographic databases, linked to analysis with IRAMUTEQ® software and in parallel with the use of governmental databases of financial content of the municipality in question. Results: after searches carried out in information resources in a systematic way, according to the PICo strategy and the PRISMA tool, 54 news were found that after in-depth reading and selection according to pre-defined criteria, 9 news remained within the scope of the research. With the analyzes carried out by the software, 6 classes of words were generated, and in this article only 2 were discussed. -19. Conclusions: It is concluded that the floriculture sector was severely affected, especially small producers. Compensatory actions were carried out with the support of the Federal Government, highlighting economic measures to help rural producers affected by the Coronavirus pandemic.